Adult health in the time of drought - Hoddinott, John F.; Kinsey, Bill (International Food Policy Research Institute, 2003)
It is a well-known fact that households in developing countries often undergo weather-related and other shocks that drastically affect incomes. A large and growing literature explores the effectiveness of response to these events. One strand of the literature addresses the strategies that households and governments use to protect against income shocks (Udry 1990; Fafchamps, Udry, and Czukas 1998; Kochar 1999). A second strand looks at the effectiveness of these strategies in reducing fluctuations in consumption. The principal result, summarized in Morduch (1995, 1999a) and Townsend (1995), is that some, but not all, households are able to smooth consumption. Households facing liquidity constraints, in particular, have limited smoothing ability. For these households, income fluctuations lead to a welfare loss.